The Use Of Problem Based Learning (PBL) To Increase Students’ Achievement In Reading Comprehension At The Eight Grade Of Smp Swasta Prama Artha - Tiodora Fermiska Silalahi; Anita Purba; Rindi Dwi Septi (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The aim of this research is to find out the using of Problem Based Learning The Students’ Achievement In Reading Comprehension At Eight Grade Students’ of SMP Swasta Prama Artha Academic Year 2022/2023. The researcher used quantitative approach with pre-experimental research design. Population of this research was eight grade with three classes which consists of 136 students and the sample of research was 34 students in one class. The technique of collecting data was pre-test and post-test. The technique of analysis data by using calculating formula. The result of this research was TO > Ttable 5% < Ttable 1% (15,637 >1,692 < 2,733) so that the statistic criterion of accepted hyphotesis exists in Hyphotesis alternative (Ha) and Hyphotesis null (Ho) is rejected. It means that, the use of Problem Based Learning to increase students’ achievement in freading compmrehension at the eight grade SMP Swasta Prama Artha in academic year 2022/2023 is significant to increase students’s achievement in reading comprehension